2015 8th International Congress on Image and Signal Processing (CISP) 2015
DOI: 10.1109/cisp.2015.7408076
|View full text |Cite
|
Sign up to set email alerts
|

A novel chicken voice recognition method using the orthogonal matching pursuit algorithm

Abstract: In an ecological breeding environment, feeders usually don't know whether their chicken are in good condition. Fortunately, Chicken voices reveal a lot of messages and it is easy to access and process voice signals. Therefore, we propose a newtype chicken voice recognition method using sparse representation aiming at the chicken voice recognition problem in an ecological breeding environment. In future, the method can be used in chickens for automated disease detection during the period of the bird flu. First,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 19 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…In addition, in the signal filtering method of this article, we choose the first method to determine the iterative stop condition of Sparse Decomposition. The author checked the relevant literature and found that Cheng et al [ 14 ] had also conducted the research on broiler signal filtering. In her research, when Sparse Decomposition is used for signal filtering, the second method is selected to determine the iterative stop condition, and the achieved signal filtering effect is excellent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in the signal filtering method of this article, we choose the first method to determine the iterative stop condition of Sparse Decomposition. The author checked the relevant literature and found that Cheng et al [ 14 ] had also conducted the research on broiler signal filtering. In her research, when Sparse Decomposition is used for signal filtering, the second method is selected to determine the iterative stop condition, and the achieved signal filtering effect is excellent.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in his research mentioned above, Carpentier, Lenn et al [ 10 ] used Spectral Subtraction to filter the sound signal before extracting features from broilers’ sneezes. Cheng et al [ 14 ] proposed a new broiler sound recognition method based on Sparse Representation. Specifically, it used Sparse Representation to reconstruct the sound signal, to complete signal filtering and feature extraction, and also used the SVM as the classification model to recognize the broiler sound in different environments.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lee et al [ 10 ] used the Support Vector Machine (SVM) as a classification model to identify the sound types while the laying hens suffered physical stress from changes in temperature and mental stress from fear. Cheng et al [ 11 ] proposed a new-type chicken voice recognition method. This method used sparse representation to complete the noise reduction and feature extraction from the reconstructed voices.…”
Section: Introductionmentioning
confidence: 99%